THE IMPORTANCE OF THE LISBON TREATY. MAIN CHANGES AND THEIR ROLE IN THE CONSTRUCTION OF THE EUROPEAN UNION - Honorius CIRCA (Challenges of the Knowledge Society)
Analyzing the “Europe 2020” Strategy means analyzing the concepts of intelligent, durable and social-inclusion and social-dialogue friendly growth. In this context, the Lisbon Treaty appears as the supplier of a judicial basis for the enactment of the Lisbon Strategy and the “Europe 2020” Strategy stands as an instrument for enacting the Lisbon Treaty. Furthermore, the European social model emerges not merely as a symbiosis of the different national models of the Member States, one being thus able to debate on its global uniqueness. Concerning this aspect, we place a heavy emphasis on the analysis of the possible implications the compulsory character of the Charter has, in addition to the increasing role of the social partners within the EU.